Special Exercises and their Impact on the Development of Some Types of Muscular Ability, Functional Variables, and Digital Level of Runners (200m Freestyle) for Physical Disability (T 46) Men - Ibrahim, Waleed Jaleel; Ahmed, Emad Khathim; Hameed, Ahmed Walhan; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The importance of this research is to highlight the importance of using special exercises for the 200 meter free run for persons with physical disabilities in category (T46) and their effect on the development of some types of muscular ability related to skill performance and outstanding achievement. The researchers sought to prepare special exercises, thus developing scientific and practical solutions to one of the training problems. The aim of the research was to prepare special exercises, which defined the effect of special exercises in some types of muscular and digital abilities in individuals. After the data was processed statistically, the researchers reached a number of conclusions, the most important of which were the following: The special exercises applied to the sample resulted in an improvement in the strength of the arms, legs and trunk, and the development of the power level characteristic of speed during performance. Researchers use special exercises to develop the rapid capacity of other groups with disabilities.